Evaluation of soil potassium‐holding capacity based on waterlogging‐simulation experiments. (17th May 2021) - Zhao, Xinlin; Gao, Shuaishuai; Lu, Dianjun; Chen, Xiaoqin; Wang, Huoyan; Zhou, Jianmin
Abstract: Evaluating the capacity and loss risk of soil nutrients is helpful to make fertilization strategies. Herein, the term of soil potassium (K)‐holding capacity (SKHC) was put forward to assess the capacity and loss risk of plant‐available K of specific soils. In this study, SKHC was evaluated via soil waterlogging‐simulation experiments using 14 different soils. The K concentrations in surface water were measured, and a critical K concentration was selected to indicate high soil K loss. Results showed that the surface water K concentration (Ksw ) was significantly affected by waterlogging time, temperature, and soil thickness. The average Ksw of 5‐cm soil columns waterlogged for 24 h for the 14 soils was 5 mg L –1 (1.57–8.57 mg L –1 ); this was subsequently used as the critical K concentration. By repeating the waterlogging simulation experiment with soils treated with different rates of K fertilizer, a quadratic relationship between the K rate and Ksw was found and used to determine the K rate required making the Ksw reach the critical K concentration. For the 14 soils, SKHC ranged from 133 to 2, 054 mg kg –1 and can be classified into four levels: low,  <500 mg kg –1 ; moderate, 500–1, 000 mg kg –1 ; high, 1, 000–1, 500 mg kg –‐1 ; and extremely high,  >1, 500 mg kg –1 . These results allowed the preliminary establishment of an SKHC evaluation method and grading system. Future studies should verify the SKHC under field conditions and optimize the assessment method proposed in this study. Core Ideas: Soil K‐holding capacity refers to the highest plant‐available K under low risk of loss. Sodium tetraphenylborate is an ideal extractant for extracting plant‐available K. Soil potassium‐holding capacity was evaluated via waterlogging simulation experiments. Soil potassium‐holding capacity can be used to direct K application with low loss.